Scabies and impetigo prevalence and risk factors in Fiji: a national survey. - Lucia Romani; Josefa Koroivueta; Andrew C Steer; Mike Kama; John M Kaldor; Handan Wand; Mohammed Hamid; Margot J Whitfeld (PLoS Neglected Tropical Diseases, 2015)
BACKGROUND:Scabies is recognised as a major public health problem in many countries, and is responsible for significant morbidity due to secondary bacterial infection of the skin causing impetigo, abscesses and cellulitis, that can in turn lead to serious systemic complications such as septicaemia, kidney disease and, potentially, rheumatic heart disease. Despite the apparent burden of disease in many countries, there have been few large-scale surveys of scabies prevalence or risk factors. We undertook a population-based survey in Fiji of scabies and impetigo to evaluate the magnitude of the problem and inform public health strategies. METHODOLOGY/PRINCIPAL FINDINGS:A total of 75 communities, including villages and settlements in both urban and rural areas, were randomly selected from 305 communities across the four administrative divisions, and all residents in each location were invited to participate in skin examination by trained personnel. The study enrolled 10,887 participants. The prevalence of scabies was 23.6%, and when adjusted for age structure and geographic location based on census data, the estimated national prevalence was 18.5%. The prevalence was highest in children aged five to nine years (43.7%), followed by children aged less than five (36.5%), and there was also an indication of prevalence increasing again in older age. The prevalence of scabies was twice as high in iTaukei (indigenous) Fijians compared to Indo-Fijians. The prevalence of impetigo was 19.6%, with a peak in children aged five to nine years (34.2%). Scabies was very strongly associated with impetigo, with an estimated 93% population attributable risk. CONCLUSIONS:As far as we are aware, this is the first national survey of scabies and impetigo ever conducted. We found that scabies occurs at high levels across all age groups, ethnicities, and geographical locations. Improved strategies are urgently needed to achieve control of scabies and its complications in endemic communities.